2022
DOI: 10.1186/s12872-022-02885-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum klotho levels and cardiovascular disease risk factors in older adults

Abstract: Background Klotho deficiency is a significant predictor of cardiovascular disease (CVD)-related mortality and morbidity. However, research assessing the association between klotho and individual risk factors of CVD is limited. This study aimed to explore the association between circulating serum klotho levels and risk factors for CVD in adults. Methods We used the 2007–2016 National Health and Nutrition Examination Survey and included 13,154 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…In summary, the negative correlation between plasma klotho concentration and the occurrence of cardiovascular disease (CVD) and atherosclerosis has been con rmed [29,[33][34]. This association is also observed in our study regarding the relationship between AIP and klotho.…”
Section: Results Of Subgroup Analysissupporting
confidence: 87%
“…In summary, the negative correlation between plasma klotho concentration and the occurrence of cardiovascular disease (CVD) and atherosclerosis has been con rmed [29,[33][34]. This association is also observed in our study regarding the relationship between AIP and klotho.…”
Section: Results Of Subgroup Analysissupporting
confidence: 87%
“…However, the physiological effects of sex steroid hormones on klotho levels have not been completely elucidated and require further studies. Furthermore, the only factor related to klotho level was the frequency of alcohol drinking which is in line with the previous research [121][122][123]. Quintero-Platt et al [124] observed higher s-Klotho levels among alcoholics than in controls, but these differences were dependent on the presence of cirrhosis.…”
Section: Discussionsupporting
confidence: 89%
“…In the CRS setting, high klotho levels are associated with a lower risk of decline in kidney function [ 41 ]. At the same time, lower klotho levels seem to be a potent marker of cardiovascular risk, especially in an aging situation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, low circulating plasma soluble klotho levels have been correlated with worsening renal function in chronic kidney disease (CKD) and end-stage renal disease (ESRD) as well as in acute kidney injury (AKI) [ 10 ]. Furthermore, low soluble klotho levels are associated with arterial stiffness in CKD, increased cardiovascular mortality rate in haemodialysis and cardiovascular disease risk factors in older adults [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%